Utility of the Ages and Stages Questionnaires 3rd Edition for Developmental Screening in Children with Surgically Repaired Congenital Heart Disease. (17th February 2022) - Lépine, Julien; Gagnon, Karine; Prud'homme, Joëlle; Vinay, Marie Claude; Doussau, Amélie; Fourdain, Solène; Provost, Sarah; Belval, Véronique; Bernard, Catherine; Gallagher, Anne; Poirier, Nancy; Simard, Marie-Noëlle
ABSTRACT: Aim : This study sought to evaluate the accuracy of the Ages and Stages Questionnaires 3rd Edition (ASQ-3) in identifying developmental delay (DD) in children with congenital heart disease (CHD) born at term who underwent surgical repair. Methods : Participants had to complete ASQ-3 and Bayley Scales of Infant and Toddler Development 3rd Edition (BSID-III) at 12 and 24 months. A child was considered at risk of DD for a ASQ-3 domain when he scored below the cutoff (≤-1SD or ≤-2SD). A child had a DD in a BSID-III domain when the score was ≤-1SD. The validity for each ASQ-3 domain and for overall ASQ-3 was measured. Results : At 12 months (n = 64), overall ASQ-3 (≤-2SD) sensitivity was 88%, specificity 74%. At 24 months (n = 82), overall ASQ-3 (≤-2SD) sensitivity was 74%, specificity 88%. Conclusion : The results support the utility of the ASQ-3 for screening the overall risk of DD in children with CHD.